Diffusion de la recherche féministe dans les Amériques. Émergence, construction et consolidation d’un champ disciplinaire : Le concept de genre dans la revue Feminist Studies (1972-2013) - Estelle Lebel (Centre de Recherches sur les Mondes Américains, 2014)
The journals disseminating Feminist Research are communication channels needed for sharing, questioning, confrontation and consolidation of knowledge on women and on social gender relations, of theoretical underpinnings and of the political scope. Since the publication of the first issues of Feminist Studies (1972), of Women’s Studies : An Interdisciplinary Journal (1972) and among others of the still current journal Signs (1975), the Association of College & Research Librairies listed, for 2008, about forty journals in the Women and Gender Studies section; these journals contributed to the continuity and transformations of Feminist Studies in the Americas. The issues addressed, the authors’ background, for more than 40 years, contributed to establishing the credibility of feminist issues on scientific bases. These publications are obviously in English and are excluded from this list South American and Mexican journals, including the excellent Brazilian journal Revista Estudos Feminista (1992), publishing in Spanish and in Portuguese, and the Quebec and Francophone journal Recherches féministes (1987), that have to be added to reflect the diversity of themes and approaches and provide an overview of the evolution of the field in the Americas.